Natural Killer Cell-Derived IL-10 Prevents Liver Damage During Sustained Murine Cytomegalovirus Infection - Ali, Alaa Kassim; Komal, Amandeep Kaur; Almutairi, Saeedah Musaed; Lee, Seung-Hwan (Frontiers in Immunology, 2019)
Natural Killer (NK) cells are lymphocytes of the innate immune response that play a vital role in controlling infections and cancer. Their pro-inflammatory role has been well established; however, less is known about the regulatory functions of NK cells, in particular, their production of the anti-inflammatory cytokine IL-10. In this study, we investigated the immunoregulatory function of NK cells during MCMV infection and demonstrated that NK cells are major producers of IL-10 during the early stage of infection. To investigate the effect of NK cell-derived IL-10, we have generated NK cell-specific IL-10-deficient mice (NKp46-Cre-Il10fl/fl) displaying no signs of age-related spontaneous inflammation, with NK cells that show no detectable IL-10 production upon in vitro stimulation. In NKp46-Cre-Il10fl/fl mice, the levels of IL-10 and IFNγ, viral burdens and T cell activation were similar between NKp46-Cre-Il10fl/fl mice and their control littermates, suggesting that NK cell-derived IL-10 is dispensable during acute MCMV infection in immunocompetent hosts. In perforin-deficient mice that show a more sustained infection, NK cells produce more sustained levels of IL-10. By crossing NKp46-Cre-Il10fl/fl mice with perforin-deficient mice, we demonstrated that NK cell-derived IL-10 regulates T cell activation, prevents liver damage, and allows for better disease outcome. Taken together, NK cell-derived IL-10 can be critical in regulating the immune response during early phases of infection and therefore protecting the host from excessive immunopathology.